2018
DOI: 10.1115/1.4039002
|View full text |Cite
|
Sign up to set email alerts
|

Branch Reconfiguration of Bricard Linkages Based on Toroids Intersections: Plane-Symmetric Case

Abstract: This paper for the first time reveals a set of special plane-symmetric Bricard linkages with various branches of reconfiguration by means of intersection of two generating toroids, and presents a complete theory of the branch reconfiguration of the Bricard plane-symmetric linkages. An analysis of the intersection of these two toroids reveals the presence of coincident conical singularities, which lead to design of the plane-symmetric linkages that evolve to spherical 4R linkages. By examining the tangents to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…In this paper, this idea was extended to the spatial case in order to design spatial 1-DOF cusp mechanisms. It was found that a simple way of dealing with curves traced by spatial mechanisms is the use of intersection of surfaces generated [26,28,29,44] by kinematic dyads. Using this method, three examples were presented.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper, this idea was extended to the spatial case in order to design spatial 1-DOF cusp mechanisms. It was found that a simple way of dealing with curves traced by spatial mechanisms is the use of intersection of surfaces generated [26,28,29,44] by kinematic dyads. Using this method, three examples were presented.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this paper a method for the design of spatial 1-DOF mechanisms with cusp singularities is presented as a means to generate test cases facilitating such research. This method is based in the intersection of surfaces [26][27][28][29]. In addition, a planar mechanism with a higher-order cusp singularity is presented using the same idea applied by Connelly and Servatius [8] in the design of the double-Watt mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Point A 2b which in the ideal Exechon robot is fixed and coincident with A 2a is now moving in a toroid S [22,23,24] as shown in figure 7. The common perpendicular between axes S 21 and S 22 intersects the later at point A 2c .…”
Section: Analysis Of the Parallel Module For The Ikpmentioning
confidence: 99%